1996
DOI: 10.1016/0028-3932(96)00046-2
|View full text |Cite
|
Sign up to set email alerts
|

The lateralization of lip-reading: A second look

Abstract: Abstract--Photographs of unfamiliar speaking faces were matched by normal right-handed subjects on the basis of perceived mouthshape (i.e. visible speech sound) across different face-views. A clear left-hemisphere (RVF) processing advantage emerged, which was absent when the task was that of identity matching. In contrast to earlier proposals, the extraction of lip-shape from face photographs may be better managed by left-hemisphere-than right-hemisphere mechanisms even at its initial stages. This may contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
2
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
5
30
2
1
Order By: Relevance
“…This is in agreement with previous results on laterality in lipreading [Campbell et al, 1996;Smeele et al, 1998]. Also heard speech is strongly left lateralized in subjects [for review see Tervaniemi and Hugdahl, 2003].…”
Section: Discussionsupporting
confidence: 82%
“…This is in agreement with previous results on laterality in lipreading [Campbell et al, 1996;Smeele et al, 1998]. Also heard speech is strongly left lateralized in subjects [for review see Tervaniemi and Hugdahl, 2003].…”
Section: Discussionsupporting
confidence: 82%
“…The reported visual field advantages are, however, not fully consistent. Although both left-field (R. Campbell, 1986) and right-field (R. Campbell, de Gelder, & de Haan, 1996) advantages have been observed for static face tasks, a right visual field advantage was reported for silent speechreading (Smeele, Massaro, Cohen, & Sittig, 1998). Two other studies (Baynes, Funnell, & Fowler, 1994;Diesch, 1995) also showed a right visual field advantage for the audiovisual fusion effect provided by incongruent McGurk stimuli such as ours.…”
Section: Resultsmentioning
confidence: 43%
“…Facial speech refers to characteristic shapes of lips, teeth, tongue, jaw, and cheeks (Schweinberger & Soukup, 1998). A double dissociation between deficits in analyzing identity and facial speech in brain-lesioned patients (Campbell, Landis, & Regard, 1986), as well as data from healthy persons that indicate right hemisphere usage for face identity processing versus left hemisphere usage for facial speech processing, indirectly suggests an independent mode of processing (Campbell, de Gelder, & de Haan, 1996). In addition, Campbell, Brooks, and colleagues (1996) showed more directly that facial speech perception is processed independently of face identity by demonstrating that familiarity of faces did not facilitate categorization of lip speech pictures.…”
Section: Processing Facial Identity and Facial Speech In Adults And Cmentioning
confidence: 97%